2021
DOI: 10.1097/aln.0000000000003951
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Incisional Pain after Noncardiac Surgery: An International Prospective Cohort Study

Abstract: Background The purpose of this study was to determine the incidence, characteristics, impact, and risk factors associated with persistent incisional pain. The hypothesis was that patient demographics and perioperative interventions are associated with persistent pain. Methods This was a secondary analysis of an international prospective cohort study from 2012 to 2014. This study included patients who were 45 yr of age or olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 44 publications
1
23
1
Order By: Relevance
“…Clinical outcomes following operatively managed fractures of the extremities are variable and many patients continue to experience persistent pain and disability after surgery [ 11 ]. A prospective international cohort study of 14,831 patients that underwent non-cardiac surgery found that the highest prevalence of persistent pain at 12 months was associated with orthopedic surgery [ 12 ]. A 2006 systematic review of 20 observational studies of traumatic tibial fracture repairs found that 47% of patients experienced persistent post-surgical pain at an average of 24 months after surgery [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical outcomes following operatively managed fractures of the extremities are variable and many patients continue to experience persistent pain and disability after surgery [ 11 ]. A prospective international cohort study of 14,831 patients that underwent non-cardiac surgery found that the highest prevalence of persistent pain at 12 months was associated with orthopedic surgery [ 12 ]. A 2006 systematic review of 20 observational studies of traumatic tibial fracture repairs found that 47% of patients experienced persistent post-surgical pain at an average of 24 months after surgery [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 Multimodal analgesia has been defined as the use of two or more analgesics or techniques that target different mechanisms or pathways in the nociceptive system. 4 As drugs are combined, lower doses of each class can be given, thereby lowering the side effects of each individual drug, but increasing overall efficacy. 5,6 Drugs commonly used in this framework include acetaminophen, non-steroidal anti-inflammatory drugs (NSAID) or cyclo-oxygenase-2 inhibitors, dexamethasone, gabapentin, clonidine, dexmedetomidine, intravenous lidocaine, magnesium and ketamine.…”
Section: Sp36mentioning
confidence: 99%
“…3 A very recent publication (2021) assessing incisional pain at one year after non-cardiac surgery in a cohort of 14000 patients found an incidence of 3.3% with nearly half reporting moderate (35%) to severe (14%) pain. 4 Among the patients with CPSP, 85% mentioned interference with daily activities and more than 50% were taking analgesic medications. These very recent observations are in agreement with the earlier findings mentioning that 14 to 24% of patients experience suboptimal physical and emotional recovery at 6 to 12 months after surgery.…”
mentioning
confidence: 99%
“…3 Multimodal analgesia has been defined as the use of two or more analgesics or techniques that target different mechanisms or pathways in the nociceptive system. 4 As drugs are combined,…”
mentioning
confidence: 99%